Pemberdayaan Budaya Lokal sebagai Aset di Kampung Wisata Prenggan-Yogyakarta - Fauziah, Ismahani; Naufal, Muhammad; Riswandi, Muh Syahlan; Ulhaq, M. Jia (Pusat Pengabdian kepada Masyarakat (PPKM) Universitas Prasetiya Mulya, 2025)
Community empowerment based on tourism villages aims to create a symbiotic relationship between tourism and the local community, where both parties benefit. At the same time, it also promotes cultural and environmental preservation while improving the livelihoods of local residents. Prenggan Tourism Village is located in Prenggan Subdistrict, Kotagede District, and holds valuable cultural heritage, including handicrafts, traditional arts, and distinctive Javanese architecture. In addition to its many heritage buildings, this tourism village also offers various handicrafts such as silverwork and batik. Community empowerment in Prenggan Tourism Village follows three stages: awareness through socialization, capacity-building through training and seminars, and resource mobilization with financial assistance to manage the tourism village. Meanwhile, the cultural preservation process in this village includes registering heritage buildings, conducting maintenance or conservation, organizing cultural activities involving various stakeholders, and raising public awareness to preserve cultural heritage.